Bajo la sombra de la independencia: Gran Pará, la compleja red política en la crisis del Antiguo Régimen portugués - André Roberto de A. Machado (Nuevo mundo - Mundos Nuevos, 2013)
The independence of Brazil and the integration of the province of Grão Pará to the nascent Empire are such significant events for historiography that they ended for reducing all the political effervescence to this fact, in this period and in this area. Instead, this article intends to demonstrate that in the center of the disputes among the Pará people was much more than the rupture or maintenance of the ties with Lisbon. Besides, far from a predictable ending, the subordination of Pará to the Court in Rio de Janeiro only became viable in reason of an unstable conjuncture, what became uncertain the political destiny of that area until 1825 at least.